Спонтанна флора Національного ботанічного саду імені М.М. Гришка НАН України (м. Київ). Повідомлення 4. Адвентивні види: ксенофіти - Shynder, O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective — to study the species composition and structure of spontaneous flora in M.M. Gryshko National Botanical Garden of the NAS of Ukraine (Kyiv); to summarize the information on the size and structure of the spontaneous flora of the introductory institutions of Ukraine. Material and methods. The study was conducted in 2010–2018 on the territory of the M.M. Gryshko Botanical Garden of the NAS of Ukraine. Results. The list contains 123 taxa xenophytes, which is 18.9 % of the total spontaneous flora of M.M. Gryshko National Botanical Garden of the NAS of Ukraine. Probably, for the first time, 3 species of alien plants are presented for the urban flora of Kyiv: Acalypha australis, Anthriscus caucalis, Erysimum cuspidatum. Comparison of spontaneous flora of botanical gardens and arboretums of Ukraine is carried out. Conclusions. The entire xenophytes group in the botanical garden has an agricultural character. Colonies of new plants in Kyiv are now isolated, but with the preservation of existing conditions their populations will increase, while Anthriscus caucalis has a preconditions for further expansion. It is established that the dependence of the wealth of spontaneous flora of botanical gardens and arboretums on their area is not linear, but much more complex. The factors contributing to the large floristic diversity of such territories are highlighted. It is noted that in Ukraine there are no unified methodological approaches to studying the structure of spontaneous flora of botanical gardens and arboretums.